Urgensi Memahami Karakteristik Mahasiswa Universitas Katolik Widya Mandira Kupang dalam Pembelajaran pada Kurikulum Merdeka - Mulik, Cindy Esterina N.; Nelo, Yolanda Salesiana; Dhundu, Maria Gego (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research aims to identify the urgency of understanding the characteristics of Widya Mandira Kupang Catholic University (Unwira) students in the context of learning based on the Merdeka Curriculum. The Merdeka Curriculum aims to create relevant, flexible and meaningful learning, by giving students the freedom to develop their potential holistically. The research uses a descriptive qualitative method through literature study, by analyzing 5 relevant literature sources in the last four years. The research results show that understanding student characteristics, including cognitive, social, emotional and cultural aspects, is crucial to supporting the successful implementation of the Independent Curriculum. Lecturers who understand student characteristics can adopt inclusive and adaptive learning strategies, increasing student engagement, motivation and learning outcomes. In addition, this approach helps create a learning environment that supports the development of 21st century skills and students' readiness to face the challenges of the professional and social world. This research recommends training lecturers, strengthening technological infrastructure, collaborating with students, and continuing research to increase the effectiveness of learning at Unwira. Thus, a deep understanding of student characteristics is a key element in creating higher education that is responsive, inclusive and relevant to today's needs.